A gravidade do efêmero: prosa-Haicai em Rakushisha de Adriana Lisboa - Pinheiro, Samuel Delgado [UNIFESP] (2017)
Hut of fallen Permissions is the fourth Adriana Lisboa’s novel published in 2007. The narrative is about Celina who, after her husband Marco and her daughter Alice died, meets Haruki, Japanese descendent that had been invited to go to Japan to study and work on illustrations of Matsuo Bashō’s Diary of Saga. After a casual meeting in the Rio de Janeiro subway, Haruki invited Celina to travel with him. The narrative begins with these unknown characters who travel together to a country from which they don’t have any knowledge. During the travel around Japan, the characters discover the reasons for being together: Celina reads Bashō’s diary and, at the same time, she tries to overcome her mourning forthe loss of her family; Haruki establishes a contact with his descendants through Bashō’s diary and his involvement with the translator Yukiko Sakade. We can realize that the works of Matsuo Bashōgain importance through the readings undertook by the characters and it reflects on the language of the novel: Bashō’s works are present in the quotations of haiku and some sections of Saga Diary prose, establishing dialogs among the texts. This work is going to explore the textual procedures which put together haiku and prose on the language of the novel, not only through directquotations, but also through the presence of haiku in the prose of the novel which create a confluence between Eastern and Western cultures. The theories of intertextuality will help the reading of the Hut of fallen Permissions, corroborated by critics like Julia Kristeva (1941), Haroldo de Campos (1929- 2003), Haruo Shirane (1951), Roland Barthes (1915-1980) and Makoto Ueda (1931), who dedicated a large space of their work to the presence of Eastern aesthetics on the Western poetic production.